Budżetowanie jako instrument planowania i kontroli w zakładzie opieki zdrowotnej - Burek, Ewelina (Budgeting as an Instrument of Planning and Controlling in the Health Care Institution, 2005)
The requirement of well functioning health care institution in the reformed health care system, is proper managing. Adequate planning and controlling of health care institution activity is the base of management and budgeting is the main instrument of management. Preceding article is an attempt of analyzing the possibilities of introduction and functioning the budgeting system in health care sector. The increasing costs of health services and growing liabilities of health care institutions require special notice on the issue of planning and controlling the costs of health services. Therefore budgeting in the health care institution should be directed on cost controlling.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 94-101